Analisis Kemampuan Representasi Matematis Siswa dalam Menyelesaikan Masalah Luas Permukaan Bangun Ruang - Saila, Nurul; Sulianti, Ani; Hasanah, Uswatun (Program Studi Pendidikan Guru Madrasah Ibtidaiyah INSURI Ponorogo, 2023)
Mathematical representation ability is one of the five basic abilities which is the goal of mathematics learning. Through mathematical representation, problems that initially appear difficult and complicated can be seen more easily and simply, so that they can be presented simply and can be solved more easily. But in reality, the representation ability of elementary school students is still low. The aim of this research is to describe the mathematical representation abilities of class VI students at SD Negeri Kebonsari Kulon I Probolinggo, in solving surface area problems of geometric shapes. This research is qualitative research with a descriptive approach. The population in this study were all class VI students at SD Negeri Kebonsari Kulon I Probolinggo, totaling 19 students. The data collection method in this research is the test method. Next, the data obtained was analyzed to determine students' representational abilities in solving problems on the surface area of ​​geometric figures. The results of this research show that students' visual and symbolic mathematical representation abilities in solving mathematical problems on the surface area of ​​spatial figures can be categorized as good with a percentage of 78.94% and 89.47%, while their verbal mathematical representation abilities can be categorized as very good with a percentage of 55.26. %.